Indigestion – A Life Style Disorder with Homoeopathic Modality (Homoeopathy for All, 2022)
Indigestion is not a disease.  Indigestion is usually related to  lifestyle and what we eat and drink.  The main symptom is usually  pain or discomfort in the upper  tummy (abdomen). In addition,  other symptoms that may develop  include Bloating, Belching, Quickly  feeling full after eating, Feeling sick  (nausea) & Being sick (vomiting).  Homoeopathy is a remarkable  resource for those dealing with  digestive disorders. Homoeopathy  can be of assistance in retrieving  normal motility and treating any  psychological issues related to  gastric disorders.
Keywords: Homoeopathy; Bloating